Ceramics from Samshvilde (Georgia): A pilot archaeometric study. (December 2020) - Randazzo, L.; Gliozzo, E.; Ricca, M.; Rovella, N.; Berikashvili, D.; La Russa, M.F.
Highlights: Georgian Prehistoric and glazed medieval pottery archaeometric characterization. Multi-analytical approach. First insights for the definition of ceramic trade and production in Samshvilde (Georgia). Abstract: This archaeometric study deals with seven samples of prehistoric pottery and, for the first time in Georgian studies, thirteen samples of glazed medieval pottery. All specimens were collected at Samshvilde, the most remarkable archaeological complex in southern Georgia and believed to represent locally-manufactured products. Two additional samples of raw materials composed of clay, silt, and sand were collected near the site and used to compare composition. Several analytical techniques were applied: Optical Microscopy (OM), Scanning Electron Microscopy (SEM), Electron Probe Microanalysis (EPMA), X-ray Diffraction (XRD) and X-ray Fluorescence (XRF). The results allowed to build a complex scenario in terms of exploitation of raw materials and technological choices. The raw materials indicate a volcanic environment and correspond to the geological settings of the territory of Samshvilde. The glazed ceramics were characterised as alkali, low alkali – low lead, lead, high lead and tin-opacified mixed-alkaline lead glazes. The compositional comparisons extend from east to west and place these ceramics in the wider framework of Islamic ceramics.